Forage productivity of Gliricidia accessions on a tropical alfisol soil in Nigeria - Cobbina, J.; Atta-Krah, A.N. (1992)
Assesses the forage production of 28 accessions of Gliricidia sepium for four seasons: early and late dry season, and early and late rainy season on a tropical alfisol soil at Ibadan in Nigeria. The evaluation was over a period of 24 months after establishment. Five Gliricidia accessions of different provenance produced the highest biomass. These consistently produced 4-5 t/ha/yr of leaf dry matter over the period of evaluation. During the early dry season, 8 Gliricidia accessions exhibited the greatest leaf growth rate (over 5 kg/ha/d). Three of the Gliricidia accessions have potential for greater forage production in both high and low rainfall environments.